Economic Analysis of a Rainwater Harvesting System in a Commercial Building - C. Matos (2015)
This research evaluates which is the most cost-efficient rainwater harvesting (RWH)system in a new commercial building located in the north of Portugal, in Braga. Based on theeconomic analysis, the cost-efficiency of the presented RWH strategies may be considered forthe case studied.The results of this research indicate that RWH scenarios proposed are cost-efficient.Considering a 10 % discount rate, the water price charge in the municipally of Braga andthe cost of the infrastructures would be enough to make RWH cost-efficient for this option. Atthis discount rate, the payback period ranges from 2 to 6 years and the internal rate of returnwould range from 23 to 76 %. If a discount rate of 5 % were considered, the payback periodswould be reduced by approximately 1 year.